Synergistic Response Mechanisms in Rice Seedlings Exposed to Brown Planthopper Infestation and High-Temperature Stress - Danyun Cao; Yuchen Ping; Yiru Lin; Jinyan Hu; Zimeng Wang; Wei Yuan; Tongtong Li; Linxin Liu; Bo Zhang; Shijiao Xiong; Cong Dang; Dawei Xue (Plants)
Recently, rice yield has been severely affected by both brown planthopper (BPH, Nilaparvata lugens) infestation and high-temperature stress. Numerous previous studies have identified genes conferring resistance to BPH and high-temperature tolerance in rice, respectively. However, it remains unclear how rice synergistically responds to these two stress factors. In the present study, we found that pre-treatment with high temperature can enhance rice seeding resistance to BPH, while BPH feeding did not alter the high-temperature tolerance of rice. This result can be elucidated by the subsequent transcriptome analysis. Differentially expressed genes (DEGs) following high-temperature treatment were enriched in metabolic processes and phenylpropanoid biosynthesis pathways, thereby enhancing rice resistance to BPH. Further weighted gene co-expression network analysis (WGCNA) indicated that genes in the magenta and black modules were predominantly associated with the protein folding and transmembrane transport biological processes. And several candidate genes, including Loc_Os01g02170 and Loc_Os01g59870, were identified that may play crucial roles in simultaneously regulating rice resistance to BPH and high-temperature stress. This research will provide new gene resources for cultivating rice with compound traits and provide ideas for the mechanism analysis of rice response to multiple stresses.